Revision of the genus Plesiochara Sawada (Coleoptera: Staphylinidae: Aleocharinae) - Inoue, Shûgo; Maruyama, Munetoshi (Zootaxa, 2022)
The Japanese species of the genus Plesiochara Sawada, 1989 (tribe Aleocharini) are revised. Four species are recognized from Japan: Plesiochara japonica (Sharp, 1874) comb. nov. (removed from Ocalea Erichson), P. nitida Sawada, 1990, P. inflexa sp. nov. and P. rufula sp. nov. Plesiochara fusca Sawada, 1989 is synonymized with P. japonica, syn. nov. All species are described or redescribed, and a key is provided.